2016
DOI: 10.1177/1687814016657254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rail materials and axle loads on the wear behavior of wheel/rail steels

Abstract: Four kinds of rail steels were tested to investigate the wear behaviors of wheel-rail materials under three kinds of axle loads. Results indicate that the increase in axle load not only significantly enlarges the wear loss but also enlarges the depth and the length of the fatigue cracks. However, with the decreases in the hardness ratios, some ripples are exhibited on the surface, and the wear surfaces become much rougher; the subsurface analyses deliver the presence of extremely rough surface, and the deforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…Therefore, besides the influence of the contact pressure, rolling velocity and slip ratio, the friction coefficient could also be affected by the microstructural properties of materials. In the present study, it is proved that the bainitic steel behaves a lower friction coefficient at the large axle load, which may be opposite with the results in pearlitic steels [ 37 ]. The influence of microstructural features, such as work hardening behavior, surface roughness or elastic-plastic deformation behaviors, on the friction coefficient should be deeply studied in the future work.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Therefore, besides the influence of the contact pressure, rolling velocity and slip ratio, the friction coefficient could also be affected by the microstructural properties of materials. In the present study, it is proved that the bainitic steel behaves a lower friction coefficient at the large axle load, which may be opposite with the results in pearlitic steels [ 37 ]. The influence of microstructural features, such as work hardening behavior, surface roughness or elastic-plastic deformation behaviors, on the friction coefficient should be deeply studied in the future work.…”
Section: Discussionmentioning
confidence: 82%
“…Comparison with the wear behaviors of pearlite rail steels in paper [ 37 ], the authors found that the increases in axle loads enlarged the friction coefficient significantly, and the values were about 0.36, 0.42, and 0.53 for the axle loads of 16, 21, and 25 t, respectively. However, based on the research of Chen et al [ 38 ], the influence of the axle load on the adhesion of wheel and rail was not proportional, but the adhesion depended on the surface roughness and the running speed of a vehicle.…”
Section: Discussionmentioning
confidence: 99%
“…Load, contact pressure and shear stress for solo thermal loading as well as for equivalent mechanical load for different temperatures of wheel due to braking can be obtained using equations (15). The values obtained by these equations and by FEA are in good agreement.…”
Section: Modeling Of Data From Fea and Hertz Theorymentioning
confidence: 82%
“…Properties of CL60-wheel, U71Mn50-rail materials. 14,15 Modulus of elasticity (GPa): corresponding dimensions of contact patch, deformation and contact stresses at the interface. Figure 6 shows the contact patch at the interface due to combined thermal and mechanical loading.…”
Section: Combined Loading Conditionmentioning
confidence: 99%
“…8). To determine the chemical composition of the metal, an ARC-MET 8000 Mobile Lab optical emission analyzer was used [12]. Measurements were made at three different points, three times, at the top, in the web and at the base of the wing.…”
mentioning
confidence: 99%